Aspergillus fumigatus calcium-responsive transcription factors regulate cell wall architecture promoting stress tolerance, virulence and caspofungin resistance. - Patrícia Alves de Castro; Ana Cristina Colabardini; Adriana Oliveira Manfiolli; Jéssica Chiaratto; Lilian Pereira Silva; Eliciane Cevolani Mattos; Giuseppe Palmisano; Fausto Almeida; Gabriela Felix Persinoti; Laure Nicolas Annick Ries; Laura Mellado; Marina Campos Rocha; et al. (PLoS Genetics)
Aspergillus fumigatus causes invasive aspergillosis, the most common life-threatening fungal disease of immuno-compromised humans. The treatment of disseminated infections with antifungal drugs, including echinocandin cell wall biosynthesis inhibitors, is increasingly challenging due to the rise of drug-resistant pathogens. The fungal calcium responsive calcineurin-CrzA pathway influences cell morphology, cell wall composition, virulence, and echinocandin resistance. A screen of 395 A. fumigatus transcription factor mutants identified nine transcription factors important to calcium stress tolerance, including CrzA and ZipD. Here, comparative transcriptomics revealed CrzA and ZipD regulated the expression of shared and unique gene networks, suggesting they participate in both converged and distinct stress response mechanisms. CrzA and ZipD additively promoted calcium stress tolerance. However, ZipD also regulated cell wall organization, osmotic stress tolerance and echinocandin resistance. The absence of ZipD in A. fumigatus caused a significant virulence reduction in immunodeficient and immunocompetent mice. The ΔzipD mutant displayed altered cell wall organization and composition, while being more susceptible to macrophage killing and eliciting an increased pro-inflammatory cytokine response. A higher number of neutrophils, macrophages and activated macrophages were found in ΔzipD infected mice lungs. Collectively, this shows that ZipD-mediated regulation of the fungal cell wall contributes to the evasion of pro-inflammatory responses and tolerance of echinocandin antifungals, and in turn promoting virulence and complicating treatment options.